Tensions in SMEs’ networks for sustainable entrepreneurship - Ceschel, Federico; Lucarno, Martina; Marchiori, Michela; Tunisini, Annalisa (Piccola Impresa / Small Business, 2024)
Purpose. The study analyses how organisational actors overcome internal network problems and implement solutions in SMEs' network contracts focused on sustainability objectives to leverage networking value. Design/methodology/approach. The study uses a qualitative approach to investigate possible tensions emerging in a business network with sustainability goals. Seven case studies of network contracts were analysed using the interpretative model by Tunisini and Marchiori (2020), which consists of five variables: Individual, Structural, Legitimacy, Interactions, and Governance. Findings. The research has effectively recognised different challenges and shared methods entrepreneurs often face to overcome these critical issues. The knowledge acquired from this study can be pivotal in creating proactive or responsive approaches to tackle business network difficulties. Legitimacy issues within variables carry significant weight, especially in sustainable networks, as they are difficult to address directly. Although external factors may be helpful during start-up, they can become uncontrollable obstacles for entrepreneurs in developing the network. Practical and Social Implications. The paper presents research-based recommendations for SMEs to overcome tensions and achieve external legitimacy through supplier support and customer recognition of added value. It also proposes effective management practices and regulatory guidance for policymakers. Originality of the study. While the benefits of business networking and interaction have been primarily emphasised, research on the problems and tensions in interaction and networking still needs improvement. This paper has tried to develop a deeper analysis of the concrete problems that can emerge in business networks, with particular attention paid to those SMEs networks that aim to reach sustainability goals.